Peningkatan Kemampuan Mengajar melalui Supervisi Akademik Model Lesson Study Bagi Guru PAI Gugus V Sekolah Dasar Kecamatan Godean - Mursiyam (Jurnal Pendidikan Madrasah, 2020)
The study aims to implement the academic supervision of the model lesson study to improve the ability of PAI teachers. This research uses collaborative methods involving researchers and supervisors. The subject of research is GPAI construction of the group V UPT Yandik Godean Sleman in Lesson 2019/2020. This research is an action study that implemented twice the cycle of the Kemmis and Taggart models. Each cycle includes four stages: planning, implementation, observation and reflection. Data analysis methods using qualitative analysis. The results showed an increase in teaching quality, at a cycle I with an average value of 76.4 increased to 86.3 very good qualifications, the value of the implementation of academic supervision from 85 to 92.5, the average outcome of the test post value increased from the 73.0 value with sufficient qualifications to be 78.2 with good qualifications. The study concluded that the implementation of the Academic supervision model lesson study can improve the teaching ability of PAI teachers V-Group, Yandik Godean, Sleman in Lesson 2019/2020.